Spaceballs [videorecording (DVD)] - Brooks, Mel, 1926-; Candy, John; Moranis, Rick; Pullman, Bill; Zuniga, Daphne, 1962- (MGM Home Entertainment, 2000)
A parody of epic science fiction movies, especially the original "Star wars" trilogy. Two space bums attempt to rescue a space princess from an assortment of space villains.